Barriers and enablers to walking in individuals with intermittent claudication: A systematic review to conceptualize a relevant and patient-centered program. - Ukachukwu Abaraogu; Elochukwu Ezenwankwo; Philippa Dall; Garry Tew; Wesley Stuart; Julie Brittenden; Chris Seenan (PLoS ONE)
Background Walking limitation in patients with peripheral arterial disease (PAD) and intermittent claudication (IC) contributes to poorer disease outcomes. Identifying and examining barriers to walking may be an important step in developing a comprehensive patient-centered self-management intervention to promote walking in this population. Aim To systematically review the literature regarding barriers and enablers to walking exercise in individuals with IC. Methods A systematic review was conducted utilizing integrative review methodology. Five electronic databases and the reference lists of relevant studies were searched. Findings were categorized into personal, walking activity related, and environmental barriers and enablers using a social cognitive framework. Results Eighteen studies including quantitative (n = 12), qualitative (n = 5), and mixed method (n = 1) designs, and reporting data from a total of 4376 patients with IC, were included in the review. The most frequently reported barriers to engaging in walking were comorbid health concerns, walking induced pain, lack of knowledge (e.g. about the disease pathology and walking recommendations), and poor walking capacity. The most frequently reported enablers were cognitive coping strategies, good support systems, and receiving specific instructions to walk. Findings suggest additionally that wider behavioral and environmental obstacles should be addressed in a patient-centered self-management intervention. Conclusions This review has identified multidimensional factors influencing walking in patients with IC. Within the social cognitive framework, these factors fall within patient level factors (e.g. comorbid health concerns), walking related factors (e.g. claudication pain), and environmental factors (e.g. support systems). These factors are worth considering when developing self-management interventions to increase walking in patients with IC. Systematic review registration CRD42018070418.